Spreadsheets to teach the (RP,Q) model in an inventory management course (2013)
The use of spreadsheets to support learning processes has become a common practice used by teachers in Operations Management courses -- This paper shows a predesigned spreadsheet used in an Inventory Management course to explain the model (RP,Q) using the decision rule based in the Units Service Level (USL)